Over the counter whitening agents a concise review - Demarco, Flávio Fernando (2009)
Tooth discoloration is commonly found in the dental clinic and tooth bleaching has been considered the preferred esthetic alternative,being more conservative, safe and with predictable results. Supervised home-use of 10% Carbamide Peroxide (CP) bleaching with custom-trays is the most common bleaching procedure dispensed by dentists to their patients. The good results obtained with this technique stimulated the flourishing of new products and techniques. Over-the-counter (OTC) bleaching products appeared as a low-cost alternative to bleach discolored teeth without dentist supervision. Different OTC products are available in supermarkets, drug stores or on the Internet, including rinses, paint-on brushes, toothpastes, chewing guns, dental floss, and whitening strips. There is lack of clinical evidence regarding the safety and effectiveness of these products, being most of the studies supported by the manufacturers’. Basically, toothpastes, chewing gums, and dental floss are removal agents of superficial stains. Rinses and paint-on brushes with low levels of hydrogen peroxide have some whitening effect, but without clinical relevance. Strips present similar esthetic results and side-effects, compared to bleaching with 10% CP using trays;however, the studies have financial support from the manufacturers and were based on short term evaluations. Legislation varies widely in different countries regarding OTC dental bleaching. Concerns have appeared due to the potential abusive use of these self-medication agents, especially in young patients, with potential harmful results. Dentists should be acquainted with this kind of products to be able to inform their patients. In conclusion, there is a need for independent clinical trials to provide sufficient evidence regarding the use of OTC bleaching products.